Primerjava rezultatov veleslaloma ter izbranih telesnih razsežnosti in gibalnih sposobnosti med spoloma kategorije U14 - Puhalj, Stojan (Revija za elementarno izobraževanje, 2016)
Comparison of Giant-Slalom Results, Selected Anthropometric Measurements and Physical Fitness Tests between Female and Male Competitors in Under 14 Category. The purpose of the research was to determine whether there are any differences in selected anthropometric measurements, physical fitness tests and the average times achieved in three competitions in giant slalom between female and male alpine skiing competitors in category U14. The research was conducted on a sample of 40 categorized competitors, 20 boys M = 12.5; SD = 0.513 and 20 girls M = 12.55; SD = 0.510. Gender differences in selected anthropometric measurements (volume of the left knee, body mass index (BMI), and percentage of body fat), selected physical fitness tests (ten jumps on both legs, running eights, and test of stability), and ski result were assessed using t-test for independent samples. In order to assess ski result, average time from tree giant-slalom runs was used. Statistical significance was set at the α level of 0.05. The results showed that there were statistically significant differences (p
Keywords: alpine skiing; morphology; motor abilities